2001
DOI: 10.1128/mcb.21.16.5312-5320.2001
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Acetylated MyoD and the Bromodomain of CBP and/or p300

Abstract: Acetylation is emerging as a posttranslational modification of nuclear proteins that is essential to the regulation of transcription and that modifies transcription factor affinity for binding sites on DNA, stability, and/or nuclear localization. Here, we present both in vitro and in vivo evidence that acetylation increases the affinity of myogenic factor MyoD for acetyltransferases CBP and p300. In myogenic cells, the fraction of endogenous MyoD that is acetylated was found associated with CBP or p300. In vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
65
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 44 publications
4
65
0
Order By: Relevance
“…Consistent with previous studies demonstrating that p300 and pCAF were coactivators of MyoD (7,8,11,12,27), we observed that both of these ATs are necessary for maximal levels of transcriptional activation. Although pCAF was not sufficient for MyoD-dependent transcription, when p300 was also present, the two coactivators synergize, leading to a strong activation of transcription.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Consistent with previous studies demonstrating that p300 and pCAF were coactivators of MyoD (7,8,11,12,27), we observed that both of these ATs are necessary for maximal levels of transcriptional activation. Although pCAF was not sufficient for MyoD-dependent transcription, when p300 was also present, the two coactivators synergize, leading to a strong activation of transcription.…”
Section: Discussionsupporting
confidence: 81%
“…Thus, pCAF is probably recruited to the MyoD-bound promoter by means of p300, and this recruitment might be facilitated and͞or stabilized by the interaction between the bromodomain of pCAF and the acetylated histone H3 tail within the nucleosomes (9). Once stably associated with the promoter, pCAF then acetylates MyoD (11), which in turn could stabilize the interaction between MyoD and p300 (27) or aid in the recruitment of other bromodomain containing coactivators (28). Stable interaction between MyoD and p300 would facilitate the recruitment of the RNA Pol II transcriptional machinery by means of its ability to interact with the RNA Helicase A (29).…”
Section: Discussionmentioning
confidence: 99%
“…However, this activation was reduced to 12.5-fold when STAT3-C was cotransfected, indicating that STAT3-C suppresses transcriptional activities of MyoD. Because transcriptional activities of MyoD are crucially regulated by p300, CBP, and/or PCAF through the acetylation (37,40,41), we examined the effects of these molecules on MyoD activities suppressed by STAT3. As a result, we found that the supplement of p300, CBP, and PCAF individually restored MyoD activities suppressed by STAT3 (Fig.…”
Section: Reciprocal Inhibition Between Myod and Stat3 44184mentioning
confidence: 99%
“…In addition, the myogenic basic helix-loop-helix protein MyoD is also acetylated in myogenic cells (12). MyoD acetylation increases its transcriptional activity by influencing its ability to bind DNA (13) and to interact with other proteins (11). In vitro, MyoD is acetylated by PCAF (13).…”
mentioning
confidence: 96%
“…HATs are involved at different steps of the differentiation program; differentiation triggers the acetylation of histones on muscle-specific promoters (11). In addition, the myogenic basic helix-loop-helix protein MyoD is also acetylated in myogenic cells (12).…”
mentioning
confidence: 99%